Effect of alkaline percentages on wood plastic composites properties / Muhammad Nabil Irsyad Masir - Masir, Muhammad Nabil Irsyad (Faculty of Applied Sciences, 2015)
ABSTRACT Effect of the percentages of alkaline on the properties of wood plastic composite Was studied. The percentages used were 10%, 15%, and 25%. The size of fiber affected the bonding properties during the wood plastic composite process. The objectives were to investigate the mechanical and physical properties of wood plastic composites affected by percentages of alkaline. In this project, soda pulping was used. Bending test, tensile test, and thickness swelling test were used to determine the mechanical properties of wood plastic composite made from fiber from Kenaf and plastic pallets was used as the binder. The results obtained shows that the lesser the viscosity, more space can be covered up by fiber thus influenced the properties of wood plastic composites. Higher alkaline percentage caused more water been absorbed. The wood plastic composites properties used 10% and 15% alkaline percentages is were better than 25% alkaline percentages.